Science: The Key to Unlocking a Sustainable Future - Yekinni, Olufunmilola Taiwo; Olaleye, Bolanle Omotoke (Faculty of Natural and Applied Sciences Journal of Basic and Environmental Research, 2025)
In today’s globally interconnected and rapidly evolving world, science and technology literacy is essential for individuals to thrive professionally and in everyday life. Science drives innovation and provides sustainable solutions to global challenges. However, despite its significance, many young people are drifting away from studying science, even as their engagement with modern technology increases. This study examined the scientific background knowledge of young people and their interaction with contemporary technology. A survey design of the ex-post facto type was used, as the variables were not manipulated. The target population comprised students in higher institutions across two educational districts in Lagos State, from which 1,250 participants were randomly selected. Data were gathered using a validated and highly reliable (r = 0.98) adapted questionnaire measuring science knowledge and technology use. Descriptive statistics (frequencies, percentages, means and standard deviations) were used for analysis. Results revealed an average science background knowledge score of 52.07% and a weighted mean technology engagement score of 3.22. The study recommends that national policy should prioritise science education to promote lifelong learning and support the development of a knowledge-driven, globally connected society.